Dr. Mahmut Nuri Karatoprak — Deep Plane Facelift — Istanbul - Karatoprak, Mahmut Nuri (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Mahmut Nuri Karatoprak, practicing in Istanbul, Turkey. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003325; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; turkey; istanbul